Beberapa Faktor Risiko Kejadian Persalinan Prematur (Studi Persalinan Prematur di RSUD Hj. Anna Lasmanah Kabupaten Banjarnegara) - Yuniwiyati, Hanik; Wuryanto, Moh Arie; Yuliawati, Sri (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Preterm delivery occurs before 37 weeks gestation. One of the causes of high infant mortality rate in Banjarnegara district in 2013 due to preterm birth (36,53%). The purpose of this study was to analyze the risk factors associated with the incidence of preterm delivery. The method used was a quantitative method with case control design. This study consisted of 69 cases and 69 controls. Samples were taken by simple random sampling. Data analysis used chi square test with α= 95%. The results showed correlation between age (OR=2,412 (1,188-4,900)), hemoglobin concentration (OR=3,514 (1,631-7,571)), mid upper arm circumference (OR=2,605 (1,200-5,656)), gestational weight gain (OR= 10,384 (4,524-23,833)), history of preterm delivery (OR=9,750 (2,790-34,071), family income (OR=6,535 (3,100-13,776)), and antenatal care (OR=7,708 (3,310-17,952)) with preterm delivery. There were no correlation between parity, body mass index pre-pregnancy, status of cigaretee smoke exposure and presence concomitant diseases. Advice for Health Service by Midwife to have a personal blood test tool to measure hemoglobin levels of pregrant women, so Midwife can check and monitor status of anemic pregnant women directly and actively provide information about the risk factors for preterm delivery, partiulary weight gain according to the recommendation from Institute of Medicine. To pregnant women should be routine to do antenatal care, so the risk factor of preterm delivery can be known as soon as possible.